Pengaruh Biaya Promosi Terhadap Pendapatan Kamar di Villa Jerami & Spa Pada Masa Pandemi Covid-19 - Adinda, Clearesta; Prabawati, Ni Putu Diah; Prateka, I Wayan Reza Cahyadi (Program Studi Administrasi Perhotelan, 2023)
Decreased room revenue can reduce revenue, because room revenue contributes the largest revenue, ranging from 60-70% of all hotel revenues. Room revenue is income from the sale of rooms used or rented by guests staying at the hotel with various types of payment methods. Factors that can affect room revenue in order to get the maximum profit is the cost of promotion. This study aims to determine the effect of promotional costs on room revenue at Villa Jerami & Spa. The data collection used are interviews and documentation studies, by analyzing secondary data related to promotion costs and room income. Data were analyzed using descriptive analysis and simple linear regression assisted by SPSS version 26 for Windows. The results of the study indicate that the promotion costs partially have a positive and significant effect on room income. The results also obtained from the hypothesis testing t test value tcount > ttable = 6.663 > 1.689 and significance value < 0.05 = 0.000 <. Based on the analysis of the coefficient of determination of promotion costs, it has a strong contribution of 56.6% and the remaining 43.4% is influenced by other variables not examined in this study.